(3GdEbJUGO GdfbOj hGdHfcj (B/s - (3dWQT, GdWGgQs ((3GdLRGFQ(B: s (3GdOjhGf GdeWHhYGJ GdLGeYjI(B, s, 2015)
(3jYGdL gPG GdcJGH Cge GdehGVjY GdJj JTcd eVehf GdGbJUGO GdfbOj hGdHfcj eKd GdCOGA GdhXjaj ddfbhO hBKGQg Ydi GdGbJUGO, hGdCOGA GdhXjaj ddfXGe GdfbOj hGdHfcj hGdYdGbGJ GdfbOjI Hjf echfGJg hHGbj echfGJ GdGbJUGO aVdG Yf GdSdhc GdfbOj ddCYhGf GdGbJUGOjjf hSHd VHWg(B. (3hbO JhNi GdcGJH aj eYGdLI gPg GdehGVjY efgLG eHSWG Ohf Cf jaJbO Edi GdObI GdeWdhHI(B. (3ceG MQU Ydi JhXja ebGQHI efOeLI ddeSGFd GdfbOjI GdOGNdjI hGdNGQLjI fXQG dCf GdbQGQGJ GdfbOjI ZjQ eJLRCI hJJLGhR JOGYjGJgG GdOGFQI GdJj JJNP ajgG(B. (3Je JfGhd cd gPg GdehGVjY aj CQHYI eMGhQ eHhHI HTcd eOQhS hgj(B: (3GdfbhO hGdfXGe GdfbOj, MQcI GdfbhO aj GdGbJUGO hVHW COGFgG, GdeSGFd GdfbOjI aj EWGQ GdYdGbGJ GdGbJUGOjI GdNGQLjI hCNjQG GdfXGe GdfbOj GdLRGFQj(B.s
(3GdeQGLY U(B.427s
Keywords: (3GdEbJUGO GdfbOjs; (3GdSjGSI GdfbOjIs